Family Support as a Determinant of Elderly Welfare: Evidence from Balung District, Jember - Mahmudi, M. Hafid; Ramadhansyah, Ariangga; Haq, Yusdi (Jurnal Sosiologi Agama Indonesia (JSAI), 2025)
Indonesia is facing a rapid demographic transition as its elderly population continues to rise, posing new challenges for social and health policy. Family support is widely recognized as a crucial factor in elderly well-being, but there is limited empirical evidence from local Indonesian contexts, particularly in rural areas such as Balung District, Jember. This study aims to examine the influence of family support on the welfare of elderly individuals in Balung District, Jember, and to determine how much variance in elderly welfare can be explained by family support. A quantitative cross-sectional design was employed. Data were collected from 70 respondents—35 elderly people and 35 family caregivers—using purposive sampling. Validated and reliable instruments measured family support and elderly welfare. Pearson correlation and simple linear regression analyses were conducted using JASP software. The findings reveal a strong positive relationship between family support and elderly welfare (r = 0.688, p < 0.001). Family support accounted for 47.4% of the variance in elderly welfare. The analysis confirms that higher levels of family support are significantly associated with improved well-being among the elderly. Family support is a key determinant of elderly welfare in Balung District, Jember. Programs and policies that empower and educate families, enhance community resources, and strengthen family-based care systems are essential for improving the quality of life of Indonesia’s aging population. Future research should explore additional factors influencing elderly welfare and adopt mixed-methods approaches for a more comprehensive understanding.